The secret art of chip graffiti. - Goldstein, H. (IEEE spectrum)
Chip designers have often etched whimsical imagery onto their creations, but as automated tools improved and design cycles shrank, so did companies' tolerance for the improvised extras. This article looks at the history of chip graffiti, its evolution with IC design techniques and scaling, and chip art's decreasing prevalence due to increased production pressures and sophisticated design automation techniques such as VHDL